2018
DOI: 10.1364/ao.57.003796
|View full text |Cite
|
Sign up to set email alerts
|

Piezo-, elasto- and acousto-optic properties of Tl3AsS4 crystals

Abstract: Complete matrices of piezo-optic and elasto-optic tensors are experimentally determined for TlAsS crystals. It is revealed that the piezo-optic coefficients are very high, ∼10 N/m in the order of magnitude. This implies that TlAsS can be referred to the best piezo-optic materials. The same concerns the elasto-optic coefficients, of which absolute values are in the interval 0.28-0.54. It is also found that, at the anisotropic and isotropic interactions with the slowest transverse and longitudinal acoustic waves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…These parameters are respectively equal to p 31  0.27, p 32  0.32 and p 33  0.39 (at 632.8 nm   ), and determined under the conditions of isotropic interactions of the optical waves polarized along the crystallographic axis c with the longitudinal acoustic waves propagating along the crystallographic axes. It would be worthwhile to remind in this respect that the velocity of the quasi-longitudinal wave does not manifest essential anisotropy, varying from 2077 to 2369 m/s [7]. On the other hand, the so-called principal EOCs lie in the region 0.28-0.54 and so can change almost twice.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…These parameters are respectively equal to p 31  0.27, p 32  0.32 and p 33  0.39 (at 632.8 nm   ), and determined under the conditions of isotropic interactions of the optical waves polarized along the crystallographic axis c with the longitudinal acoustic waves propagating along the crystallographic axes. It would be worthwhile to remind in this respect that the velocity of the quasi-longitudinal wave does not manifest essential anisotropy, varying from 2077 to 2369 m/s [7]. On the other hand, the so-called principal EOCs lie in the region 0.28-0.54 and so can change almost twice.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, Tl 3 AsS 4 is a promising material for thermal imaging [6]. Recently, we have determined the complete matrices of piezooptic and elastooptic coefficients (EOCs) [7] for the Tl 3 AsS 4 crystals, together with the complete matrices of elastic stiffness and compliance coefficients [8]. It has been found that the piezooptic coefficients are very high, being 10 -11 N/m 2 in the order of magnitude.…”
Section: Introductionmentioning
confidence: 99%